Oral oligofructose challenge reduces expression of glucose transport-1 and 5′-adenosine monophosphate-activated protein kinase in lamellar wall of Holstein heifer claw. (December 2021) - Li, Y.P.; Ding, J.F.; Abid, H.M.; Zhang, X.H.; Li, S.C.; Song, Q.Z.; Jiang, L.H.; Zhang, J.T.; Wang, H.B.
Abstract: The laminar tissue of bovine laminitis may undergo energy failure. The expression of glucose transport protein-1 (GLUT-1) and 5′-adenosine monophosphate-activated protein kinase (AMPK) affects the energy metabolism of digital laminar tissue. This study aimed to determine the expression of glucose uptake and AMPK in laminar wall corium of Holstein heifer claw by oral administration of oligofructose. A total of twelve clinically healthy Holstein heifers were selected and divided into two groups, including control (CON, n = 6) and experimental (OF, n = 6) groups. The heifers of OF group were given 17 g/kg BW oligofructose dissolved in water (20 mL/kg BW) and the heifers of CON group were given water only (20 mL/kg BW). The laminar tissues were collected after euthanasia. The amount of protein and transcript expression of AMPK and GLUT-1 were determined by western blot and quantitative reverse transcription-polymerase chain reaction (qRT-PCR), respectively. Expressions of phosphoenolpyruvate carboxy-kinase (PEPCK), receptor-c coactivator1-α (PGC-1α) and peroxisome proliferator-activated receptor-γ (PPAR-γ) were determined by qRT-PCR. The heifers of OF group showed no significant change in the expression and concentration of AMPK. The phosphor-(Thr172) AMPK and GLUT-1 were significantly decreased, while the gene contents of PPAR-γ and PGC-1α were significantly increased. The activation of AMPK and GLUT-1 in digital laminar tissues of heifers was inhibited, which may contribute to digital laminar tissue damage. Highlights: Oral oligofructose challenge lead to bovine laminitis. Bovine laminitis lead to GlUT-1 and AMPK expression were inhibited. Study the changes of energy metabolism in acute laminitis.